Analisis Arus Kas Operasional dan Likuiditas Jangka Pendek (Studi Kasus: Perusahaan Ritel Mainan di Surabaya) - Widyadana, Ayudhia Sakha; Seputro, Dimas Nugroho Dwi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Cash flow is a critical indicator of a company’s short-term financial health, especially for retail businesses with high transaction volumes and fluctuating cash movements. Toy retail companies, in particular, often face challenges in maintaining operational liquidity due to inconsistent sales cycles and fixed operational expenses. This study aims to analyze the operational cash flow condition and the short-term liquidity capacity of a toy retail company in Surabaya. The research adopts a quantitative descriptive approach using secondary data derived from the company’s cash flow statement for the first quarter of 2025. Data were analyzed through trend analysis (month-to-month growth), operating cash flow to current liabilities ratio (OCF/CL), and cash ratio to assess liquidity adequacy. The results show that the company’s operating cash flow was unstable, with significant fluctuations observed across the three months. The OCF/CL ratio remained below 1 in all periods, indicating that operating cash flow alone was insufficient to cover short-term liabilities. Meanwhile, the cash ratio consistently exceeded 1, suggesting that liquidity was supported by cash reserves rather than operating performance. This discrepancy highlights a potential risk of future liquidity stress if reliance on cash reserves continues. The study concludes that while the company appears financially stable on the surface, it must improve operational cash flow management to ensure sustainable liquidity. Future research should consider a longer observation period and the inclusion of additional financial ratios for a more comprehensive assessment.